Penerapan Formulir KTP Berbasis Android: Studi Pada Kantor Camat Rantau Utara Kabupaten Labuhanbatu - Silestian, Selvi; Sumitro, Sumitro; Purnama, Iwan (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2018)
The making of this android based ID card application aims to: 1) Provide convenience for the community in filling in the form of ID card without having to come to the office requesting form because it can be filled wherever they are using a smartphone; 2) Accelerate the process of service and making ID cards. The method used waterfall and programming used in the writing of this Final Project is based on android programming using mysql database for php script creation. In this application required internet or wifi facility of a mobile phone, which where the application can run if the application has been installed connected on the mobile phone in a network. From the discussion on the form of ID based on android can be concluded that: 1) With the application of this android ID based form, the process of inputting population data can be done quickly and efficiency without having to go to the office to fill out the ID; 2) With the application of this android ID based form, the service and making ID card (identity card) can be easier and faster; 3) Processing of population data on the application of this android ID based ID will facilitate the work process so as to improve the performance of the institution later; 4) Have built an Android based ID application form designed using UML (Unified Modeling Language) and implemented using Eclipse for Android Application using PHP and MySQL programming language and for its database online in one network